2020
DOI: 10.31083/j.jin.2020.02.19
|View full text |Cite
|
Sign up to set email alerts
|

Topological properties of the resting-state functional network in nonsyndromic cleft lip and palate children after speech rehabilitation

Abstract: Speech therapy has been widely used as an essential therapy for compensatory articulation errors in nonsyndromic cleft lip and palate patients. We sought to identify potential biomarkers of nonsyndromic cleft lip and palate children after speech rehabilitation based on resting-state fMRI and graph theory techniques. We scanned 28 nonsyndromic cleft lip and palate and 28 typically developing children for resting-state fMRI on a 3T MRI scanner. Functional networks were constructed, and their topological properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The lower σ suggested a disturbance of the average balance and a higher cost for a new equilibrium between weaker local phonologic information transfer and higher global information integration, demonstrating a random network tendency in articulation-rehabilitated children with NSCLP (22). However, our previous study showed that the same participants exhibited a higher σ value of the resting-state functional network in the NSCLP group (11).…”
Section: Small-world Propertiesmentioning
confidence: 72%
See 1 more Smart Citation
“…The lower σ suggested a disturbance of the average balance and a higher cost for a new equilibrium between weaker local phonologic information transfer and higher global information integration, demonstrating a random network tendency in articulation-rehabilitated children with NSCLP (22). However, our previous study showed that the same participants exhibited a higher σ value of the resting-state functional network in the NSCLP group (11).…”
Section: Small-world Propertiesmentioning
confidence: 72%
“…Our recent study based on restingstate functional MRI that detected the increased capability of information transmission and integration involving language and social cognition brain areas in children with CLP after articulation rehabilitation. In addition, we found an increased small-world index in these patients which means optimum equilibrium between local specialization and global integration to process information (11). The structural organization of CLP children in the developing brain after articulation rehabilitation still needs to be investigated.…”
Section: Introductionmentioning
confidence: 84%
“…We presumed that the increased modularity index was linked with the higher degree strength and betweenness centrality induced by the repair surgery and speech therapy, which improved network adaption (Guye et al, 2010). Our previous study found the increased small-world index in children with CLP after speech rehabilitation (Rao et al, 2020). We can infer that the higher modularity index caused the small-world index to increase for the function specialization.…”
Section: Ta B L E 3 Statistical Analysis Of Modular and Global Metricsmentioning
confidence: 90%
“…Another study of adult speech‐rehabilitated patients with CLP showed similar functional activation patterns as healthy controls, except for increased activation in the left hippocampus in a subvocalization task functional MRI study (Zhang et al., 2017). Our previous study found lower nodal shortest path length and higher nodal clustering coefficient of brain regions involved in higher‐order language and social cognition, and increased small‐world index of the whole brain in children with CLP after speech rehabilitation (Rao et al., 2020). Therefore, we performed a further study of the topological organization in the developing functional brain networks of children with CLP after speech rehabilitation.…”
Section: Introductionmentioning
confidence: 91%
“…Articulation disorder is one of the developmental motor-speech disordersthat can persist into adulthood [ 15 ]. Previous studies have shown a correlation between articulation function and brain activation in CLP patients [ 16 , 17 ]. CLP subjects recovered to a normal level of articulation function after speech training, while their language-related brain function was improved [ 18 ].…”
Section: Introductionmentioning
confidence: 99%